Pengaruh cash holding, foreign ownership, struktur modal, dan perputaran modal kerja terhadap nilai perusahaan - Roza, Fania Devara; Mashuri, Ayunita Ajengtiyas Saputri (Jurnal STEI Ekonomi, 2023)
This study aims to determine the effect of cash holding, foreign ownership, capital structure, and working capital turnover on the firm value. The population used in the study was consumer goods industry sector companies listed on the Indonesia Stock Exchange in 2019-2021 with sample selection based on several criteria that have been set. The Data used in the study is quantitative data obtained from the company's annual report. Data analysis techniques using multiple linear regression processed using STATA version 14. The results showed that cash holding has a positive effect on the firm value, foreign ownership has a negative effect on the firm value, capital structure does not positively affect the firm value and working capital turnover does not positively affect the firm value.